CDKN2A exon 1B deletion predisposing to melanoma and neural system tumour syndrome. (25th October 2022) - Wong, Samantha L.; Martiniuc, Daniela; Kiuru, Maija
Abstract : CDKN2A at chromosome positon 9p21 is a tumour suppressor gene encoding the cell cycle regulators p16 and p14ARF. While melanoma is associated with variants affecting both transcripts, families with mutations involving the p14ARF‐specific exon 1B may be predisposed to central nervous system tumours. We describe a family with a deletion of exon 1B in CDKN2A, who had multiple cutaneous melanomas, neural tumours and various malignancies.